ТЕХНОЛОГІЧНЕ ЗАБЕЗПЕЧЕННЯ ПРОЦЕСУ РОЗВИТКУ ТВОРЧОГО МИСЛЕННЯ МАЙБУТНЬОГО ПЕДАГОГА (Педагогіка вищої та середньої школи, 2007)
This article deals with modern pedagogical technologies and the author's approach to the development of the future teacher’s creative personality on the basis of development of creative pedagogical thinking are suggested.